The Readiness Of Prospective Hotel Workers In Facing The Acceleration Of Tourism Development In Labuan Bajo: Kesiapan Calon Tenaga Kerja Perhotelan Dalam Menghadapi Percepatan Pembangunan Pariwisata Di Labuan Bajo - Elisabet Oktaviani Hanggu; Dea Arme Tiara Harahap; Gregorius Antariksa Berybe (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This research was conducted to determine the readiness of the hotel workforce in Labuan Bajo during the acceleration of tourism development. Respondents in this study were the hotel industry that used student services to expedite hotel operations during the ASEAN SUMMIT 2023 in Labuan Bajo. Based on the results of the research, it can be concluded that industry perceptions of students' abilities to communicate, work together in teams, independence, creativity, basic hospitality skills, and self-appearance are considered ready to face the world of work